Immunogenicity and Predictive Factors Associated with Poor Response after Severe Acute Respiratory Syndrome Coronavirus 2 Vaccination in Lung Transplant Patients - Se Ju Lee; Ala Woo; Jung Ah Lee; Yongseop Lee; Ha Eun Kim; Jin Gu Lee; Song Yee Kim; Moo Suk Park; Su Jin Jeong (Vaccines, 2024)
Lung transplant patients are more likely to develop severe coronavirus disease 2019 (COVID-19) compared with the general population and should be vaccinated against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, previous studies have reported reduced vaccination immunogenicity in lung transplantation patients. We aimed to investigate the serological response and associated factors after SARS-CoV-2 vaccination in this population. Lung transplant patients without a history of contracting coronavirus disease who had received a second or higher dose of SARS-CoV-2 vaccination were enrolled. The anti-SARS-Cov-2 spike and neutralizing antibody levels were measured in blood samples. Firth’s logistic regression analysis was performed to assess the factors associated with non-response after vaccination. Forty-six lung transplant patients were enrolled, of which sixteen (34.8%) showed a serological response to vaccination. All patients who received anti-SARS-CoV-2 vaccination before transplantation (n = 5) exhibited a serological response. No significant difference was observed in anti-SARS-CoV-2 S antibody or neutralization titers based on the number and timing of vaccination. Firth’s logistic regression showed an association between lower hemoglobin levels (odds ratio, 0.59; confidence interval, 0.35–0.92; p = 0.017) and non-response to SARS-CoV-2 vaccination. Lung transplant patients showed poor serologic responses after SARS-CoV-2 vaccination in this pilot study; anemia may be associated with this poor response.